(untitled) (Fiep Bulletin - online, 2011)
This paper presents a reflection on the Human Movement, an object of study in Science of Sports/Physical Education from the culture of the movement parameters of physical efficiency and/or technical in modern sport. In contrast to these parameters also presents the possible contributions of communicative action theory of German philosopher and sociologist Jürgen Habermas for Human Movement said in a dialogical perspective, as the expression of the for their emancipation. Keywords: Human Movement; Emancipation; Habermas.